PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL MEREK DALAM KONTEKS : PARFUM LOKAL MENIRU GLOBAL - Rere, Krisencia Indah Permata Celina (Ensiklopedia Education Review, 2025)
Abstract: The rise of local "inspired perfumes" in Indonesia raises legal issues around trademark protection and fair competition. These products often mimic global perfume brands in name, packaging, and marketing, potentially violating laws like the Trademark Act and the Unfair Business Competition Law. This paper discusses misleading naming, design imitation, and pricing tactics that leverage brand association. Despite claims that the similarities are limited to fragrance or inspiration, using registered brand elements still risks deceiving consumers and damaging the original brand’s reputation. Enforcing intellectual property rights is crucial to ensure fair competition and protect consumers.Keywords: Inspired Perfume, Trademark Infringement, Unfair Competition, Consumer Rights, Intellectual Property Rights.